2019
DOI: 10.3390/nano9121756
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Graphite Pencil Lead as a Cheap Alternative for Classic Conductive SPM Probes

Abstract: This paper presents polymer graphite (PG) as a novel material for the scanning tunneling microscopy (STM) probe. Conductive PG is a relatively modern nanocomposite material used for micro-pencil refills containing a polymer-based binding agent and graphite flakes. Its high conductivity and immunity against surface contamination, with a low price, make it seem like a highly suitable material for electrode manufacturing in general. For the tip production, three methods were developed and are further described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 14 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…The graphite pencil rods have generally two main constituents: graphite itself and various clay minerals or rocks, which are finely ground (small amounts of wax or polymers are also present to serve as a binder) [ 11 , 14 ]. It was reported that polymer graphite contains usually from 30% up to 80% of sp 3 hybridized carbon which may shift its properties more toward those of diamond-like carbon (DLC) structures [ 11 ]. The macroscopic hardness of polymer graphite rod is determined by the graphite–clay ratio.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The graphite pencil rods have generally two main constituents: graphite itself and various clay minerals or rocks, which are finely ground (small amounts of wax or polymers are also present to serve as a binder) [ 11 , 14 ]. It was reported that polymer graphite contains usually from 30% up to 80% of sp 3 hybridized carbon which may shift its properties more toward those of diamond-like carbon (DLC) structures [ 11 ]. The macroscopic hardness of polymer graphite rod is determined by the graphite–clay ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Graphite-based materials such as graphene are also capable of replacing conventional capacitors as its electrical characteristics 10–100 times exceed those of the currently used material—silicon (100 times thinner, 20 times more powerful, significantly superior electrical conductivity, etc.). Graphite-related carbon allotropes are also often incorporated as a source of field emission current in vacuum [ 8 , 9 , 10 ] or as a source of tunneling current operating both in vacuum and in atmospheric conditions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations